Droppings, Adding, And Spelling Deviations In Georgia Doyle Jhonson's Fredrick Douglas And Loraine Hansberry's (A Rais In The Sun) - Sadiq, Nizamuddin (English Education Department, Universitas Islam Indonesia, 2008)
Language is reflected by pronunciation, syntax, and lexicon. So is the American African English. A sit is considered non-standard dialect, the American African English pronunciation is assumed to have its own characteristic different from the standard American. English. Furthermore, according to a linguist, pronunciation of a community is clearly patterned and systematic. Therefore, the purpose of this paper is to describe pronunciation of the American African English in Georgia Doyle Johnson's Frederick Douglas And Loraine Hansbeiry's A Raisin In The Sun, in the viewpoints of droppings, addings, and spelling derivations.This paper is descriptive linguistics rather than a stylistic study as it does not focus on literary style. The data taken was classified into linguistic elements and was tested to the theories of informal English in general; African American English in particular and Standard American English rules of pronunciation. The research findings were summarized and discussed to conclude the research.The result of the research demonstrates that African American English, a variant of informal English, is different from the rules of Standard American English In terms of pronunciation, African American English speakers tend to pronounce words as they like. Therefore, the pronunciations of words are very different from Standard English Words maybe dropped or shortened and some additional sounds included or changed. Words such as jes', fallin', 'em, fore', mo', yo' cap'n, yes'm, alissenin', figger, bleve, sho, enuf, wus, whut, mek, s'ed, agin, git, lak, yaw, ur, yore, etc. frequently occur and are common in African American English. Thus, African American English pronunciation is difficult to understand and strange for students of non-English speaking countries.